Fear of flying: Components and forms of coping with a group of Patagonians living in relative isolation - Luis Mimica, Jose; Castillo, Gonzalo; Estrada Goic, Claudia Andrea (My University, 2018)
This study is about the fear of flight, the danger expectations and the coping strategies that people say to use when flying on an airplane. A total of 287 participants, people from a graphically isolated zone that usually use planes, were measured according to the already mentioned variables. The sampling was not accidental probabilistic and the designed used was not experimental transversal correlational. The principal results indicate that people say to be afraid principally of situations that cause in them the loss of the emotional control, although, their most common coping strategies use to be oriented to affront anxiety. This strategy, aimed to regain the psychological control symbolically, does not point to the emotions coping. Also, some differences in the use of these strategies according to gender are described. These results are discussed regarding its timing with previous studies and their potential implications for current therapeutic intervention programs for this problem.
Keywords: fear of flight; coping strategies; danger expectations